Thermal-electronic behaviors investigation of knitted heating fabrics based on silver plating compound yarns. Issue 13 (August 2016) - Liu, Hao; Li, Jin; Chen, Li; Liu, Li; Li, Yafang; Li, Xiaojiu; Li, Xiaojie; Yang, Haile
In this paper, three kinds of knitted heating fabrics (KHFs) were designed and fabricated by using silver plating compound yarns (SPCYs) and polyester staple fiber spun yarns (PSFSYs), and thermo-electric properties of KHFs and SPCYs were investigated by performing a series of experiments. Experimental results showed, with increasing ageing time and ageing temperature, the breaking strength of PSFSYs and SPCYs had nearly not changed, but resistances of SPCYs increased markedly. After performing 264 hours ageing at 120℃ environment temperature, resistances of SPCYs exceeded the measuring range of the multi-meter. By taking and analyzing infrared temperature images of KHFs and SPCYs, strong linear correlation can be observed between surface maximum equilibrium temperature (SMET) of KHFs and SPCYs and power consumption density. Furthermore, strong linear positive correlation is between power consumption density of KHFs and inner equilibrium temperature of mimetic clothing. KHFs will have wide application prospect in active warming field because of a lot of advantages, such as an even surface temperature field in the heating process, structure simplicity, flexibility, etc.